Ecological Momentary Assessment for the Evaluation of the Adherence to the Mediterranean Diet in the Context of Clinical Trials. (29th May 2020) - Boronat, Anna; Clivillé-Pérez, Joana; Otero, Eduard; Soldevila, Natàlia; Schröder, Helmut; Forcano, Laura; Pizarro, Neus; Torre, Rafael de la
Abstract: Objectives: The validation of tailored dietary Ecological Momentary Assessments (EMAs) to evaluate the continuous adherence to the Mediterranean Diet (MedDiet) for its use in the framework of nutritional intervention clinical studies. Methods: We have developed a set of dietary mobile-app EMAs to evaluate the consumption of characteristics components key in the MedDiet. The EMAs will capture the frequency of consumption of the MedDiet products during a week and extract the rate of adherence to the MedDiet. A total of 100 healthy adults were enrolled on a trial to validate the use of EMAs as a novel screener of the MedDiet adherence. Participants received on their phone four randomized questions every day for 8 weeks. The questions were semi-qualitative and enquired for their intake diet on the last hours. The validity of the EMAs is compared with two validated questionnaires: Mediterranean Diet adherence screener (MEDAS) and a food frequency questionnaire (FFQ), both validated for the Spanish population. The levels of certain urinary dietetic biomarkers associated with the MedDiet was measured during the study. Tyrosol and hydroxytyrosol (two biomarkers of olive oil consumption) and alcohol biomarkers and free fatty acids were measured. Results: A preliminary analysis of 21 subjects showed the capacity of EMAs to capture the adherence to the MedDiet, ranging in this population from 25–80% of adherence to the MedDiet recommendations. Scores obtained were correlated with the ones obtained in MEDAS, and the food frequencies captured in EMAs correlated with the frequencies reported in the FFQ at the end of the study. Individuals with higher scores in EMAs presented higher urinary levels of tyrosol and hydroxytyrosol. Participants reported a change in their dietary habits following their participation in the study, suggesting an additional beneficial effect of the EMAs. Conclusions: The tailored EMAs are a reliable dietary assessment tool that provides an improved MedDiet adherence scoring while reducing participant's burden and capturing an accurate and continuous representation of the habitual dietary patterns. Moreover, they can be used to reinforce nutritional intervention and its sustainability. Funding Sources: Alzheimer's Association and Instituto de Salud Carlos III of Spain.